2013
DOI: 10.1016/j.bios.2013.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Sensing lectin–glycan interactions using lectin super-microarrays and glycans labeled with dye-doped silica nanoparticles

Abstract: A new microarray platform, based on lectin super-microarrays and glycans labeled with dye-doped nanoparticles, has been developed to study glycan-lectin interactions. Glycan ligands were conjugated onto fluorescein-doped silica nanoparticles (FSNPs) using a general photocoupling chemistry to afford FSNP-labeled glycan probes. Lectins were printed on epoxy slides in duplicate sets to generate lectin super-microarrays where multiple assays could be carried out simultaneously in each lectin microarray. Thus, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 70 publications
0
51
1
Order By: Relevance
“…The residual was then dissolved in methanol-d 4 together with methyl pentafluorobenzoate as the internal standard for 19 F NMR analysis. 19 …”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The residual was then dissolved in methanol-d 4 together with methyl pentafluorobenzoate as the internal standard for 19 F NMR analysis. 19 …”
Section: Methodsmentioning
confidence: 97%
“…19 F NMR spectra of (A) PFPA-SNPs after treatment with aqueous HF, (B) PFPA-silane, (C) Man-SNPs after treatment with aqueous HF, (D) compound 7. Peak (F-4) from methyl pentafluorobenzoate standard is marked as "S".…”
mentioning
confidence: 99%
“…For the photoinitiated carbohydrate conjugation to SNPs, a method developed in our laboratory the nanoparticles were first functionalized with PFPA-silane, after which the carbohydrates were conjugated by irradiation in the presence of carbohydrates. Using this methodology we have for example prepared carbohydrate-functionalized SNPs from different mono- and oligosaccharides [15, 76, 122124]. …”
Section: Preparation Of Glyconanomaterialsmentioning
confidence: 99%
“…The high specific surface area allows the nanomaterial to accommodate high-density carbohydrate ligands, enhancing carbohydrate-mediated interactions by way of multivalency. We [1015] and others [16, 17] have thus shown that the affinities of glyconanomaterials with lectins are several orders of magnitude higher than those of free ligands. Furthermore, by conjugating epitopes of more complex glycans on nanoparticles, the affinities of the resulting nanomaterials could surpass those of the original oligosaccharide glycans [12, 18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…FSNP was prepared by co-condensing tetraethyl orthosilicate with FITC-derivatized silane (Scheme 1a) 19, 20 to give particles of 30.4 ± 1.9 nm (TEM) or 38.6 ± 1.7 nm (DLS) (Fig. S1).…”
mentioning
confidence: 99%